Dendritic Fe3O4@Poly(dopamine)@PAMAM Nanocomposite as Controllable NO‐Releasing Material: A Synergistic Photothermal and NO Antibacterial Study. (3rd April 2018) - Yu, Siming; Li, Guowei; Liu, Rui; Ma, Dong; Xue, Wei
Abstract: Nowadays, antibiotic abuse increases the emergence of multidrug‐resistant bacterial strains, which is the major reason for the failure of conventional antibiotic therapies. Therefore, developing novel antibacterial materials or therapies is an urgent demand. In the present study, photothermal and NO‐releasing properties are integrated into a single nanocomposite to realize more efficient bactericidal effects. To this end, polydopamine (PDA) coated iron oxide nanocomposite (Fe3 O4 @PDA) is used as a photoconversion agent and the core, first three generation dendritic poly(amidoamine) (PAMAM‐G3) is grafted on the surface of Fe3 O4 @PDA, and subsequently NO is loaded with the formation of NONOate. The resultant Fe3 O4 @PDA@PAMAM@NONOate displays controllable NO release property under intermittent 808 nm laser irradiation and excellent bacteria‐separation efficiency. Moreover, excellent synergistic photothermal and NO antibacterial effects are observed against both Gram‐negative Escherichia coli and Gram‐positive Staphylococcus aureus, where bacterial viability and biofilm are significantly reduced. An antibacterial mechanism study reveals that the materials first adsorb onto the bacterial membrane, then cause damage to the membrane by the increased local temperature and the released NO under laser irradiation conditions, finally leak the intracellular components like DNA and induce bacteria death. The work provides a novel way for designing of antibacterial materials with higher efficiency. Abstract : In the present work, a multifunctional nanocomposite with magnetical bacteria separation, controllable NO release, and synergistic photothermal and NO antibacterial properties is designed and fabricated. Under intermittent 808 nm laser irradiation, NO release reflux can be tailored in a controllable way. The obtained nanocomposite displays significant bactericidal and biofilm eradication effects on both Gram‐negative E. coli and Gram‐positive S. aureus .